Policy, people, and the new professional : de-professionalisation and re-professionalisation in care and welfare - Duyvendak, Jan Willem; Knijn, Trudie; Kremer, Monique (Care & welfare., 2006)
An essential perspective on the latest shifts in roles of the health and welfare professionals throughout Europe.